Isoscutellarein and hypolaetin 8-glucuronides from the liverwort Marchantia berteroana - Markham, K.R.; Porter, L.J.
The major flavonoid of Marchantia berteroana is hypolaetin 8-0-fi-D-glucuronide. This is accompanied by apigenin and luteolin, isoscutellarein (8-hydroxyapigenin)8-O-/3-D-glucuronide, the 7-O-/?-D-glucuronide and -galacturonide of apigenin and luteolin, luteolin 3'-0-/?-D-glucuronide and -galacturonide, luteolin 7,3'-di-O-/3-D-glucuronide and -galacturonide, luteolin 3',4'-di-O+D-glucuronide and -galacturonide, luteolin 7,4'-di-0-P-D-glucuronide, and hypolaetin 8,4'-di-0-/?-D-glucuronide. The isoscutellarein and hypolaetin glucuronides, and the galacturonide flavones are all new natural products.